Dynamic Behaviors of a General Discrete Nonautonomous System of Plankton Allelopathy with Delays - Yaoping Chen; Fengde Chen; Zhong Li (Discrete Dynamics in Nature and Society)
We study the dynamic behaviors of a general discrete nonautonomous system of plankton allelopathy with delays. We first show that under some suitable assumption, the system is permanent. Next, by constructing a suitable Lyapunov functional, we obtain a set of sufficient conditions which guarantee the global attractivity of the two species. After that, by constructing an extinction-type Lyapunov functional, we show that under some suitable assumptions, one species will be driven to extinction. Finally, two examples together with their numerical simulations show the feasibility of the main results.